Unemployment in the Hashemite Kingdom of Jordan from 1991 Until 2013 - Hassan, Ibrahim M. (Humanities Journal of University of Zakho, 2017)
This study aims to analyze the trends and determinants of unemployment in the Hashemite Kingdom of Jordan, based on annual data for the unemployment rate as a depended variable and a number of independent variables as (money supply, foreign aid, government investment expenditure , the number of the population, inflation rate, the real interest rate, gross fixed capital formation , gross domestic product ) for a series of time stretching from 1991 until 2013, and was found by the study that unemployment rates were higher in females compared with males reaching the arithmetic average of the rate of unemployment among females (25.10%), while the average for males (12.47%) During the period of study; In addition, the rate Unemployment was highly sensitive to changes in government investment expenditure, real interest rate while he was less sensitive to changes in the money supply , foreign aid , the population growth rate , inflation rate , gross fixed capital formation , gross domestic product.